2021
DOI: 10.1002/jemt.23846
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and palynological assessment of some taxa of genus Echinochloa through light and scanning electron microscopy

Abstract: The present study was undertaken to gather information on selected species of Echinochloa based on their morphological and palyonological examination through light and scanning electron microscopy. As the Echinochloa species are most problematic grass weeds and exhibit high interspecific and intraspecific variability so due to their great morphological diversity it is difficult to recognize them. A lot of variation was observed in morphological features of studied taxa. In the present study, E. colona had more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Shaheen, Khan, Meo, and Akhtar (2005) stressed the taxonomic value of grass palynological characters by studying pollen morphology of three genera of Paniceae tribe and variations in pollen size as well in P / E ratio had been recorded. The current research of Shaheen et al (2021) reported that Echinochloa colona and Echinochloa crus‐galli can be differentiated on their pollen sizes.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…Shaheen, Khan, Meo, and Akhtar (2005) stressed the taxonomic value of grass palynological characters by studying pollen morphology of three genera of Paniceae tribe and variations in pollen size as well in P / E ratio had been recorded. The current research of Shaheen et al (2021) reported that Echinochloa colona and Echinochloa crus‐galli can be differentiated on their pollen sizes.…”
Section: Introductionmentioning
confidence: 79%
“…Paniceae tribe and variations in pollen size as well in P/E ratio had been recorded. The current research ofShaheen et al (2021) reported that Echinochloa colona and Echinochloa crus-galli can be differentiated on their pollen sizes.However, palynological data of multiple Poaceae taxa had been explored in past but still gaps found in the literature. Many of the species have been neglected and their palynological data is missing.Moreover most of these studies reported the data observed underonly light microscopy.…”
mentioning
confidence: 85%